Patients’ Experiences of Barriers and Facilitators for Adherence to Type 2 Diabetes Mellitus: A Meta-Ethnography - Sridharan, Subha Gomathy; Chittem, Mahati; Maya, Sravannthi (Journal of Social Health and Diabetes, 2019)
Objectives The main purpose of this article is to synthesize qualitative research exploring experiences of the factors that facilitated and hindered adherence among patients with type 2 diabetes mellitus (T2DM).Methods Twenty-six qualitative studies were purposefully included in the final sample. The Critical Appraisal Skills Program criteria for quality assessment of the studies was conducted. A meta-ethnographic approach proposed by Noblit and Hare (1988) was employed to analyze the studies. Using the “reciprocal translation” process, the authors searched for and consolidated the common themes.Results Three major themes were observed: (1) psychological determinants comprising illness beliefs, locus of control, and being forgetful; (2) sociocultural determinants of family and community, culture, and financial aspects; and (3) patients’ relationship with their physicians.Discussion The meta-ethnography underlines the importance of cultural nuances in the subjective experiences of the barriers and enablers of diabetes adherence. The findings support the need to include qualitative research methods to develop and evaluate interventions to improve T2DM adherence in patients. Clinical implications of this meta-ethnography include engaging in psychoeducation sessions for patients and caregivers, helping set reminders for patients, introducing communication skills training for healthcare providers, and including female caregivers/patients actively in diabetes care.
Keywords: meta-ethnography; adherence; synthesis